2017
DOI: 10.1002/2017jc012872
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence and Mixing in a Shallow Shelf Sea From Underwater Gliders

Abstract: The seasonal thermocline in shallow shelf seas acts as a natural barrier for boundary‐generated turbulence, damping scalar transport to the upper regions of the water column and controlling primary production to a certain extent. To better understand turbulence and mixing conditions within the thermocline, two unique 12 and 17 day data sets with continuous measurements of the dissipation rate of turbulent kinetic energy (ɛ) collected by autonomous underwater gliders under stratified to well‐mixed conditions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 50 publications
5
46
0
Order By: Relevance
“…The platform for our microstructure measurements was the 1,000‐m‐rated Slocum G2 ocean glider Comet , one of the gliders also used by Schultze et al (). The glider samples autonomously in a vertical sawtooth pattern, surfacing at predetermined intervals to establish a satellite link in order to update its position estimate, send low‐resolution flight and hydrography data, and receive updated sampling instructions from an onshore pilot.…”
Section: Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…The platform for our microstructure measurements was the 1,000‐m‐rated Slocum G2 ocean glider Comet , one of the gliders also used by Schultze et al (). The glider samples autonomously in a vertical sawtooth pattern, surfacing at predetermined intervals to establish a satellite link in order to update its position estimate, send low‐resolution flight and hydrography data, and receive updated sampling instructions from an onshore pilot.…”
Section: Measurementsmentioning
confidence: 99%
“…In contrast to this approach, we follow the method of Schultze et al () and use the steady state model of Merckelbach et al () to obtain the angle of attack but then use the measured pitch and pressure to estimate U dynamically using U=Wsinγ0.3em, where W is the glider's vertical velocity estimated from the measured rate‐of‐change of pressure. We found that this quasi‐dynamic estimate of U leads to more consistent results between profiles of ε from upcasts and downcasts.…”
Section: Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…can have a great impact on the ocean circulation/ecosystem state and evolution through their particular structures and transport mechanisms. Other fine scale processes are clearly involved in the ocean mixing, like microturbulence (Fer et al, 2014;Palmer et al, 2015;Schultze et al, 2017) or frontogenesis, filamentation due to stirring or symmetric instability (Figure 11 and Ruiz et al, 2012;Thompson et al, 2014Thompson et al, , 2016Thomsen et al, 2016;Pietri et al, 2013;Brannigan et al, 2017;Buffett et al, 2017;Du Plessis et al, 2017;Pascual et al, 2017;Kolodziejczyk et al, 2018) that can lead to significant vertical velocities and fluxes. However, the extent and variability of their impact over long periods of time still needs to be assessed.…”
Section: Mesoscale and Submesoscale Phenomenamentioning
confidence: 99%